650 nm red-light therapy attenuates sepsis-induced acute lung injury via adiponectin-mediated immune–metabolic reprogramming - Zhang, Yiqiu; Ni, Wei; Li, Jianghan; Bai, Yubing; Bai, Yier; Jiang, Zhixuan; Wang, Jiadie; He, Yu; Li, Yafeng; Yuan, Jing; Yao, Min (Frontiers in Immunology, 2026)
BackgroundSepsis-induced acute lung injury (ALI) is driven by dysregulated innate immunity and mitochondrial dysfunction. Monocyte/macrophage trafficking and polarization critically shape disease trajectory, yet clinically tractable immunometabolic interventions are limited. We hypothesized that 650 nm red-light photobiomodulation (PBM) alleviates septic ALI by reprogramming myeloid responses and preserving mitochondrial function via adiponectin signaling.MethodsSeptic ALI was induced by cecal ligation and puncture (CLP) in mice. Animals received 650 nm PBM (10 min, every 6 h, three times within 24 h). Survival, lung edema, histology, and serum cytokines were assessed. Lung chemokines/cytokines were profiled by 23-plex Luminex. Immune composition was analyzed by flow cytometry, and CCR2+/CX3CR1+ subsets were visualized in CcrRFP–Cx3cr1GFP mice using 3D cryo-fMOST. IHC quantified CX3CR1, CCR2, CD68, CD86, and CD206. Adiponectin was measured in serum/BALF and lung. Pathway relevance was tested by AdipoR1 siRNA. In LPS-stimulated RAW264.7 macrophages, PBM effects on cytokines, ATP, mitochondrial ROS (MitoSOX), membrane potential (JC-1), and MitoTracker fluorescence were evaluated, with/without AdipoR1 knockdown.ResultsPBM prolonged survival, reduced lung edema, improved histopathology, and lowered systemic TNF-α, IL-6, IL-1β, and MCP-1. Luminex showed broad suppression of pro-inflammatory mediators (e.g., G-/GM-CSF, IL-1 family, IL-6, IL-12, IL-17A, TNF-α) and chemokines (CCL11, CXCL1, MCP-1/CCL2, CCL3/4/5), with increases in IL-4/IL-10/IL-13. Flow cytometry revealed decreased neutrophils, monocytes, and inflammatory macrophages, alongside restored eosinophils and resident macrophages. Cryo-fMOST and IHC demonstrated reduced CCR2+/CD86+ inflammatory cells and enrichment of CX3CR1+/CD206+ reparative cells. PBM elevated adiponectin in serum, BALF, and lung; AdipoR1 knockdown abrogated anti-inflammatory effects and myeloid rebalancing. In vitro, PBM dose-dependently suppressed LPS-induced TNF-α/IL-6 and IL-1β while increasing IL-10, restored ATP, reduced mitochondrial ROS, and improved membrane potential, that benefits lost with AdipoR1 silencing.ConclusionsSeptic ALI modulated by 650 nm PBM was characterized by suppressing CCR2+ inflammatory recruitment, enriching CX3CR1+/M2-like macrophages, and preserving mitochondrial function through adiponectin–AdipoR1 signaling. These data position red-light PBM as a mechanistically grounded, non-invasive method for sepsis-associated lung injury.